A 2D → 3D Polycatenated Metal–Organic Framework: Synthesis, Structure, Magnetic and Catalytic Study. Issue 17 (22nd April 2013) - Sen, Rupam; Saha, Debraj; Mal, Dasarath; Brandão, Paula; Rogez, Guillaume; Lin, Zhi
Abstract: A mixed‐ligand 3D metal–organic framework, [Ni(1, 2‐cpd)(bpe)(H2 O)] n (1 ) [1, 2‐cpd = cis ‐cyclopentane‐1, 2‐dicarboxylate, bpe = 1, 2‐di(4‐pyridyl)ethylene], has been constructed. Topological analysis revealed that the structure is a 3‐c uninodal 2D + 2D → 3D polycatenated net with the Schläfli symbol 6 3 . The compound is catalytically active towards the epoxidation reaction in heterogeneous media. It catalyses almost all types of olefinic substrates with equal efficiency. After reaction it can be recovered quite easily and can be used for further reaction without any loss of activity for several cycles. Variable‐temperature magnetic susceptibility measurement reveals the presence of a weak antiferromagnetic interaction in compound1 . Abstract : A mixed‐ligand nickel–organic framework has been made that has a 3‐c uninodal 2D + 2D → 3D polycatenated net. It can catalyse almost all types of olefinic substrates with equal efficiency and be used for several cycles without loss of any catalytic activity.